Development Of Internet Of Things (IoT) Trainer As A Learning Media Using NodeMCU ESP32CAM - Umam, Khotibul; Abdullah, Achmad Fiqhi; Ubaidillah, Achmad; Sukri, Hanifudin; Rahmawati, Diana; Alfita, Riza (Universitas Panca Marga, 2024)
This study examines the potential and implementation of feature development on the ESP32CAM as an Internet of Things (IoT) based learning medium in the form of a trainer. This research addresses the gap in the use of the Node MCU ESP32CAM as IoT technology in educational media, which has not been widely utilized. The primary goal of this study is to analyze and explore the use of the ESP32CAM as a trainer to enhance IoT - based learning. The study employs an exploratory approach to investigate the use of the ESP32CAM, including an analysis of the application of the technology in a learning environment. Data were obtained through questionnaires distributed to experts and users/students, involving 45 students from the Elect rical Engineering program at Trunojoyo University Madura. The results of the study indicate that the IoT trainer using the Node MCU ESP32CAM is highly feasible, with an eligibility percentage of 91.08% from expert evaluations and 87.25% from user evaluations. It is hoped that the findings of this research can provide new insights into innovations in IoT use and serve as a foundational basis for further development in the related field